Locking interstitial hydrogen atoms in Pd metallenes for efficient oxygen reduction reaction - Yu Qiu; Dongxu Jiao; Hong Huang; Jiandong Wu; Mingming Wang; Tianyi Gao; Xiao Zhao; Xin Ge; Wei Zhang; Weitao Zheng; David J. Singh; Jinchang Fan; et al. (Nature Communications)
Abstract Palladium hydride (PdHx) metallenes are efficient electrocatalysts for the oxygen reduction reaction (ORR) due to their high atomic utilization and optimized oxygen binding energies modulated by interstitial hydrogen. However, their practical application is restricted by the highly unstable nature of interstitial hydrogen at working temperatures around 353 K. Here, we report that the use of Mn effectively locks hydrogen atoms within the Pd metallenes lattice, resulting in high alkaline ORR performance across a temperature range of 303–353 K. In contrast, the ORR activity of PdHx metallenes declines sharply with increasing temperature. At 353 K, the mass activity of PdMnHx metallenes at 0.95 V reaches 1.41 A mg− 1, which is 14.1 times higher than that of PdHx metallenes. Multiple spectroscopic analyses and theoretical calculations reveal that strong electronic interactions within the immiscible Pd-Mn alloy are critical for locking interstitial hydrogen, thereby enhancing the ORR activity under high temperatures.